Dry Socket and the Length of Healing Depending on the Type of the Treatment. Part two: Treatment with Ozonated Water - J. Mazánek; H. Hubálková; H. Staňková; R. Šmucler; I. Linetskiy; V. Seidler; A. Jedličková (Czech Dental Chamber, 2016)
Introduction, aim: Ozone has antimicrobial properties and wide range of effects on human body. That is why its usage in dentistry, e.g. in treatment of dry socket may be of great value. The aim of this study was to compare the effects of standard treatment method of alveolar osteitis and therapeutic modality using ozonated water. In addition the hypothesis that ozonated water in the dry socket therapy may alleviate subjective complaints and reduce treatment time by two or three days was tested. Methods: Suggested therapeutic method originated from standard procedure for alveolar osteitis treatment. The study was conducted at Oral Surgery Unit, Department of Dentistry, General University Hospital and 1st Faculty of Medicine, Charles University in Prague. 100 patients with dry socket were randomly divided in two groups of 50 patients. Ozonated water with two ozone concentrations (6 and 10 mg/l) was applied. Its local action on patient's wound lasted for one minute daily. This procedure was repeated daily until subsidence of subjective complaints and objective signs of the disorder. Results: Alveolar osteitis treatment with ozonated water lasted for three to fourth days in 98 % of patients. Symptoms alleviation arouse after its first application. Antibiotics and painkillers were not required. All patients were available to do their jobs. Clinical findings in the course of the therapy were summarized and statistically assessed. Conclusions: Dry socket therapy with ozonated water showed reduction of treatment time by six days comparing with standard method (from average 9.39 to 3.37 days). The amount of patient visits also decreased (from 4.27 to 3.37 visits). Neither antibiotics nor painkillers were administered. Sickness leave did not need to be issued; all patients were fit for work.